The labor market in the US, 2000–2020 - Daniel S. Hamermesh (IZA World of Labor, 2021)
As the largest economy in the world, the US labor market is crucial to the economic well-being of citizens worldwide as well as, of course, that of its own citizens. Since 2000 the US labor market has undergone substantial changes, reflecting the Great Recession and the Covid Recession, but also resulting from some striking trends. Most interesting have been a remarkable drop in the labor force participation rate, reversing a nearly 50-year trend; the full recovery of unemployment after 2010 and its skyrocketing in 2020; and the little-known continuing growth in post-inflation average earnings.
Keywords: E24; N32; 330; unemployment; real earnings; inequality; US